ANALISIS PENGARUH LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI BAGIAN HUMAS DAN PROTOKOL SEKRETARIAT DAERAH KABUPATEN PONOROGO - Hariyono, Pipit Setiyo; Suseno, Y. Djoko; Sutarno, Sutarno (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2019)
The purpose of this study is to determine the effect of the Work Environment and Work Discipline on Employee Performance in the Public Relations and Protocol Section of the Regional Secretariat of Ponorogo Regency. Research this uses descriptive and quantitative analysis methods. Retrieval of data in this study using census techniques, where all employees in the Public Relations and Protocol Section of Ponorogo Regency Regional Secretariat, amounting to 30 employees, were made the subject of this study. The technique of collecting data using a questionnaire. The analysis technique uses multiple linear regression and is continued by testing R square and testing hypotheses partially and simultaneously with t test and F test. From the analysis of multiple linear regression tests conducted, the results show that the Work Environment and Work Discipline have an influence on employee performance. Based on the results of t test (partial) and F test (Simultaneous) shows that the Work Environment and Work Discipline have a significant and positive influence on employee performance, where the work environment has a greater influence than work discipline. This explains that if the work environment can be created well and supported also by high employee discipline in carrying out tasks, it will be able to improve employee performance in the Public Relations and Protocol Section of Ponorogo Regency Regional Secretariat.